The Role of Organizational Culture and Leadership in Improving Hospital Employee Performance: Literature Review - Nur Indah Rahma Dilla; Zahra Andini; Nur Atifah; Selvia Ramadani; Wasiyem (Universitas Muhammadiyah Palu, 2025)
Organizational culture and leadership play pivotal roles in determining employee performance, particularly in hospitals where effective teamwork and motivation are essential. This study aims to evaluate how organizational culture and leadership styles influence employee performance through a literature review methodology. Relevant articles were sourced from databases such as Google Scholar and Garuda, focusing on publications from the last five years using keywords such as